A Quantitative Model of Bubble-Driven Business Cycles - Benjamin Larin (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
The 2007-2008 financial crisis highlighted that a turmoil in the financial sector including bursting asset price bubbles can cause pronounced and persistent fluctuations in real economic activity. This justifies the consideration of evolving and bursting asset price bubbles as another source of fluctuations in business cycle models. Business cycle models should therefore include asset price bubble as another source for fluctuations. In this paper rational asset price bubbles are incorporated into a life-cycle RBC model as first developed by Ríos (1996). The calibration of the model to the post-war US economy and the numerical solution show that the model is able to depict plausible bubble-driven business cycles. In particular, the model generates i) a higher and empirically more plausible volatility of consumption at the cost of ii) a lower and empirically less plausible contemporaneous correlation of consumption with output than the life-cycle RBC model without bubbles.
Keywords: D58; E32; E44; 330